CHSE GUIDELINES AS ONE OF THE GOVERNMENT'SEFFORTS TO PREVENT AND CONTROL THE NOVEL CORONAVIRUS DISEASE (COVID-19) IN THE IMPLEMENTATION OF INDONESIA MICE INDUSTRY - Mahadewi, Mahadewi (Journal of Indonesian Tourism and Policy Studies, 2020)
The COVID-19 pandemic that has hit Indonesia has helped change public awareness of cleanliness, health, safety and environmental sustainability (CHSE). This awareness also affects the improvement of the quality of services and products in the world of Indonesian tourism. Economic recovery affected by COVID-19 in the tourism sector, especially in the industry for organizing Meetings, Incentives, Conventions and Exhibitions (MICE) activities, needs to be done with due observance of government regulations and international guidelines regarding the implementation of MICE activities. There needs to be a practical guide for the tourism industry, especially MICE in order to prepare activities, products and services according to the relevant regulations. This study focuses on guidelines for the implementation of cleanliness, health, safety and environmental sustainability (CHSE) in organizing meetings, incentives, conventions and exhibitions (MICE) made by the Ministry of Tourism and Creative Economy. This study used a qualitative descriptive method with data collection through observation, oral interviews and literature study. This guide emphasizes the application of standard procedures for implementing MICE activities.